Detection of Circulating Tumor DNA Methylation in Diagnosis of Colorectal Cancer. Issue 8 (12th August 2021) - Xu, Fei; Yu, Shanshan; Han, Junyi; Zong, Ming; Tan, Qi; Zeng, Xin; Fan, Lieying
Abstract : INTRODUCTION: Emerging evidence has demonstrated the potential of the circulating tumor DNA (ctDNA) methylation in the application of cancer diagnosis. METHODS: Three genes including Septin9, Syndecan-2 (SDC2), and branched-chain amino acid transaminase 1 (BCAT1), which have been well demonstrated to have aberrant expression in colorectal cancer (CRC) as tumor suppressors, were selected for detection. A total of 234 peripheral plasma samples from 104 patients with CRC and 130 patients with colorectal polyps, and 60 plasma samples from healthy controls, were collected before any treatment. A real-time polymerase chain reaction-based gene panel was used to detect the methylation of Septin9, SDC2, and BCAT1. The composite score (P) was calculated according to the cycle threshold values of the 3 methylated genes using the logistic regression equation. RESULTS: The ctDNA methylation of the 3 genes had a significantly higher level in patients with CRC, compared with patients with colorectal polyps and healthy controls. The composite score (P) showed association with tumor stages in CRC but not with the tumor location (colon or rectum). In addition, BCAT1 and Septin9 showed better performance for CRC diagnosis, by which CRC was able to distinguish from polyps with sensitivity of 83.7%, specificity of 93.9%, and area under the curve of 0.908. The diagnostic efficiency was significantly improved by combining composite score (P), carcinoembryonic antigen, and fecal immunochemical test for hemoglobin (area under the curve = 0.962). DISCUSSION: The composite score (P) derived from the ctDNA methylation levels of Septin9, SDC2, and BCAT1 can be used for CRC diagnosis with high sensitivity and high specificity. A combination of ctDNA methylation, carcinoembryonic antigen, and fecal immunochemical test for hemoglobin was proved to be the most effective approach to diagnose CRC.